Hepatic ischemia-reperfusion and its effects on duodenal anastomosis healing - Oliveira, Caroline Manoela; Oliveira, Catharinne Keyth Mendes de; Almeida, Jéssica Jacinto Salviano de; Medeiros, Vítor Brasil; Nascimento, Rafael Pereira; Azevedo, Italo Medeiros; Medeiros, Aldo Cunha (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2015)
Background/objetive: The liver ischemia and reperfusion is important for procedures occurring in liver and intestinal trauma injuries that require intestinal resection and anastomosis. The aim of this study was to evaluate the influence of hepatic ischemia/reperfusion in vivo in the healing of duodenal anastomoses. Methods: Wistar rats were randomly selected and allocated into two groups of six animals each: liver ischemia/reperfusion + duodenal anastomosis group and duodenal anastomoses group. Hepatic ischemia was induced for 30 minutes by occlusion of the vessels that supply the median and lateral lobes of the liver, using a microvascular clip. In all rats the duodenum was sectioned and an end-to-end anastomosis was performed. After liver reperfusion, animals were observed for 6 days; the maximum bursting pressure of anastomoses was determined and duodenum samples were taken for histopathological examination. Results: As a result, the maximum bursting pressure of anastomosis in ischemia/reperfusion + duodenal anastomosis group (64.5±5.5mmHg) was significantly lower (p<0.001) than in duodenal anastomosis group rats (89.7±3.4mmHg). The inflammatory tissue response in ischemia/reperfusion + duodenal anastomosis group had scores higher than in duodenal anastomosis group rats (p=0.004). Conclusion: In conclusion, the hepatic ischemia-reperfusion negatively affected the healing process of duodenal anastomoses. Key words: Liver. Ischemia/reperfusion. Duodenum. Anastomosis. Healing.